2011
DOI: 10.1080/0969594x.2011.557020
|View full text |Cite
|
Sign up to set email alerts
|

Can teachers’ summative assessments produce dependable results and also enhance classroom learning?

Abstract: Summative assessments that are integrated within the daily pedagogy of teachers are problematic. Some argue that they cannot both be helpful to pedagogy and yield results that are comparable across and between schools. Others claim that there is enough evidence to show that these targets can be achieved. The project described in this paper explored how teachers might enhance their competence in summative assessment in ways which might also have a positive effect on their teaching and learning. A strategy was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 13 publications
0
54
0
8
Order By: Relevance
“…En åtgärd som har framförts för att komma till rätta med problemet är sambedömning mellan lärare (Adie et al, 2012;Black et al, 2011), något som återkommer i allmänna rekommendationer, råd och modeller till stöd för lärares arbete med bedöm-ning och betygsättning i svensk skola (Skolverket, 2009a;. När lärare tillsammans diskuterar hur styrdokument ska tolkas i relation till bedömningar av elevers prestationer förväntas de utveckla en gemensam förståelse för vad bedömningar ska gälla vilket kan stödja arbetet för likvärdig och rättvis bedömning .…”
Section: Inledningunclassified
“…En åtgärd som har framförts för att komma till rätta med problemet är sambedömning mellan lärare (Adie et al, 2012;Black et al, 2011), något som återkommer i allmänna rekommendationer, råd och modeller till stöd för lärares arbete med bedöm-ning och betygsättning i svensk skola (Skolverket, 2009a;. När lärare tillsammans diskuterar hur styrdokument ska tolkas i relation till bedömningar av elevers prestationer förväntas de utveckla en gemensam förståelse för vad bedömningar ska gälla vilket kan stödja arbetet för likvärdig och rättvis bedömning .…”
Section: Inledningunclassified
“…In a review of 30 studies, Harlen (2004) found that assessments by instructors can provide accurate summative information when specific conditions are met. Additionally, in the King's Oxfordshire Summative Assessment Project (KOSAP), a longitudinal study, teacher educators/ researchers explored strategies for enhancing the quality of summative assessments and facilitating a positive interaction between formative and summative assessment practices (Black, Harrison, Hodgen, Marshall, & Serret, 2011). Together, the two studies outline a number of conditions for quality classroom-based assessment.…”
Section: Fostering the Dependability Of Classroom-based Assessmentmentioning
confidence: 99%
“…Summative assessment can be performed in many ways (Black et al, 2010(Black et al, , 2011McTighe & O'Connor, 2005;Scriven, 1967), though written tests are still the most prevalent (Talanquer et al, 2015;Taras, 2009;Vercellati et al, 2013). However, in different fields a few researchers have come up with an idea of carrying out assessment in some alternative manners (Dochy et al, 1999;Rebello, 2011;Schuwirth & Vleuten, 2004).…”
Section: Introductionmentioning
confidence: 99%